2022
DOI: 10.3389/fmicb.2022.826386
|View full text |Cite
|
Sign up to set email alerts
|

Migration Drives the Replacement of Xanthomonas perforans Races in the Absence of Widely Deployed Resistance

Abstract: Changes in Xanthomonas race and species composition causing bacterial spot of tomato have occurred throughout the world and are often associated with epidemics. Knowledge of bacterial population structure is key for resistance discovery and deployment. We surveyed Xanthomonas spp. composition from processing tomato fields in the Midwestern United States over a 4-year period between 2017 and 2020, compared these to strains collected previously, and found that X. perforans is currently the most prevalent species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…In the spray-inoculated trial, the recombinant plants behaved similarly, with severity scores (1.6) comparable to those of the resistant control H7981. Achieving broadspectrum resistance to bacterial spot is challenging because of the complex genetic control of resistance and rapidly shifting pathogen populations (Bernal et al 2022;Rotondo et al 2022). Combinations of bacterial spot resistance genes and QTL (Bernal et al 2020;Sim et al 2015), such as QTL-11 and Xv3/Rx4 present in parent line OH08-7663, aim to combat rapid shifts in pathogenicity or virulence.…”
Section: Resultsmentioning
confidence: 99%
“…In the spray-inoculated trial, the recombinant plants behaved similarly, with severity scores (1.6) comparable to those of the resistant control H7981. Achieving broadspectrum resistance to bacterial spot is challenging because of the complex genetic control of resistance and rapidly shifting pathogen populations (Bernal et al 2022;Rotondo et al 2022). Combinations of bacterial spot resistance genes and QTL (Bernal et al 2020;Sim et al 2015), such as QTL-11 and Xv3/Rx4 present in parent line OH08-7663, aim to combat rapid shifts in pathogenicity or virulence.…”
Section: Resultsmentioning
confidence: 99%
“…The X. perforans strains we examined from the USA were assigned to core gene clusters 1, 2, 3, 4, 5, 6, and 8, suggesting repeated emergence of genetically distinct lineages in tomato production systems. The release of new varieties of plants that carry disease resistance genes can have dramatic effects on pathogen population structure due to selection to overcome host resistance 65,66 , and we have previously reported on the loss of function of effector AvrXv3 (XopAF) in X. perforans populations, which has occurred across lineages 12,36,59 . We hypothesize that changes in prevalence and distribution of lineages are not exclusively due to selection on the pathogen population but rather are associated with the multinational structure of tomato breeding and seed production, in which parental lines and geographic locations of seed production change over time 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Examination of Type III effector content at a global scale puts variation previously observed in Florida into a larger context. XopAF was present in strains collected in the 1990s (cluster 1), but absent or non-functional in most strains from Florida, Indiana Ohio, and North Carolina, USA 8,10,12,36,59 . Here, we found that xopAF was intact in many strains from seed production areas, suggesting strong selection for loss of function in commercial fruit production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizosphere soil was studied for the re-isolation of inoculated bacteria by viable count at 15 DAS (Bernal et al, 2022). Identification of re-isolated drought-tolerant PGP bacteria was done by comparing their morphology and PGP attributes (drought tolerance, IAA production, and P solubilization) to the pure colonies of inoculated bacteria as described by Yasmin et al (2016).…”
Section: Fish-clsm For Colonization Of Inoculated Droughttolerant Pgpbmentioning
confidence: 99%